Hyphenation of Hadamard encoded multiplexing liquid chromatography and circular dichroism detection to improve the signal-to-noise ratio in chiral analysis - Siegle, Alexander Florian; Trapp, Oliver (Analytical chemistry, 2015)
The hyphenation of HPLC and circular dichroism (CD) detection is a useful analytical tool that can significantly facilitate the analysis (e.g., the assignment of the configuration) and quantitation of chiral compounds. HPLC-CD chromatograms often exhibit a low signal-to-noise ratio compared to chromatograms obtained by conventional UV detection. In this study we demonstrate for the first time the hyphenation of Hadamard encoded multiplexing HPLC with circular dichroism detection where positive and negative signals overlap. Here, a macro control of the HPLC instrument that was developed for conventional HPLC was implemented in HPLC-CD. In the chiral analysis of racemic samples, exemplified for warfarin, the signal-to-noise ratio could be enhanced by an order of magnitude. The presented results highlight the great modularity of the software controlled implementation of multiplexing and its facile transfer to other detection techniques.